2013
DOI: 10.1142/s0219622013400105
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of the Decision-Making Process in Agile Teams

Abstract: This paper firstly explores the decision-making process in agile teams using scrum practices and secondly identifies factors that influence the decision-making process during the Sprint Planning and Daily Scrum Meetings. We conducted 34 semi-structuredinterviews and 18 observations across four agile teams. Our findings show that a rational decision-making process is sometimes followed in the Sprint Planning and Daily Scrum Meetings and that three factors can influence the rational decisionmaking process: sprin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
9
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 27 publications
3
9
1
Order By: Relevance
“…The designers and developers confirmed that decision-making processes are a challenge in both the Online Survey and the Pairing Study, reflecting reports elsewhere (e.g., Drury-Grogan & O'Dwyer, 2013). The online survey respondents perceived senior stakeholders' hierarchical decision-making process as a barrier to successful ASD.…”
Section: Decision-makingsupporting
confidence: 77%
See 2 more Smart Citations
“…The designers and developers confirmed that decision-making processes are a challenge in both the Online Survey and the Pairing Study, reflecting reports elsewhere (e.g., Drury-Grogan & O'Dwyer, 2013). The online survey respondents perceived senior stakeholders' hierarchical decision-making process as a barrier to successful ASD.…”
Section: Decision-makingsupporting
confidence: 77%
“…The pairing study found that success between designers and developers comes by breaking down tasks to make "small" joint decisions and iterations together in combination with using data and audience research to inform bigger, more strategic decisions by team stakeholders. The importance of the decision-making processes reflects reports elsewhere (e.g., Drury-Grogan & O'Dwyer, 2013) and show that decision-making is an on-going challenge that requires support, both at a managerial and a localised level in an organisational setting. There appears to be a strong desire from the designers and developers to improve this, providing more ownership to teams and reducing the risk-aversive culture found in the organisation.…”
Section: Making Joint Decisionsmentioning
confidence: 62%
See 1 more Smart Citation
“…In addition, ASD is perceived as too much hampered by top-down decision-making and a persisting "sign off" tradition in the organisation. This extends findings from previous research (Drury-Grogan & O'Dwyer, 2013;Moe, Aurum & Dybå, 2012) on how decision-making processes affect agile development processes.…”
supporting
confidence: 86%
“…Interestingly, the widely reported moderator of differences in experience with ASD (e.g., Drury-Grogan & O'Dwyer, 2013;Serrador & Pinto, 2015; see also Vijayasarathy & Turk 2012), does not seem to have any impact on our measures here: both the length of work as well the explicitly elicited (self-assessed) knowledge of ASD had no significant effect on moderating satisfaction with the development process.…”
Section: Discussionmentioning
confidence: 65%